L’histoire de l’ONPhI n’est pas seulement une question de perspectives: ONPhI’s History Is Not a Matter of Perspectives - Schmid, Anne-Françoise; Adkins, Taylor (Identities: Journal for Politics, Gender and Culture, 2018)
Author(s): Anne-Françoise Schmid Title (French): L’histoire de l’ONPhI n’est pas seulement une question de perspectives Title (English): ONPhI’s History Is Not a Matter of Perspectives Translated by (French to English): Taylor Adkins Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 15, No. 1-2 (Summer 2018) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 112-117 Page Count: 6 Citation (French): Anne-Françoise Schmid, “L’histoire de l’ONPhI n’est pas seulement une question de perspectives,” Identities: Journal for Politics, Gender and Culture, Vol. 15, No. 1-2 (Summer 2018): 112-117. Citation (English): Anne-Françoise Schmid, “ONPhI’s History Is Not a Matter of Perspectives,” translated from the French by Taylor Adkins, Identities: Journal for Politics, Gender and Culture, Vol. 15, No. 1-2 (Summer 2018): 112-117.